DISINTEGRASI SOSIAL DALAM KONTEN MEDIA SOSIAL FACEBOOK - Lina Herlina (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2018)
At first, social media came as a solution for the community to facilitate communication and interaction virtually. However, due to the absence of strict regulation, it later changed into a means to spread the utterances of hate in the form of certain terms. The term cannot be understood by everyone. Therefore, researchers tried to dismantle the terms used, namely in terms of meaning and also the ideology of the use of the term. As for the term utterance of hatred which is used as material for analysis, among them are the short axis people, the people of the flat earth, the people of napkins, the children of the tablecloths, the children of the lewd, the children of camels / camel urine, the people of the micin, the children of cebong, the children of the camps, and the children of the negligee. The analysis was carried out using Fairclough's theory namely the dimensions of the text, discourse practice and social practice. Meanwhile, to dismantle its ideology is by using the theory of Jagger and F. Maier which consists of context, output of text, means of rhetoric, content and ideological statements, peculiarities and positions of discourse.